PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS DELI TUA - Tarigan, Herri Novita (Jurnal Penelitian Keperawatan Medik, 2025)
Hypertension or high blood pressure is a medical condition characterized by an increase in arterial blood pressure, where systolic pressure reaches ≥140mmHg or diastolic pressure reaches ≥90mmHg. This condition increases the risk of morbidity and mortality, thus requiring comprehensive treatment. This study aims to determine the effect of progressive muscle relaxation on lowering blood pressure in hypertensive patients at the old deli health center. This research includes quantitative, the method used is quasi-experiment with a one group design pretest - posttest approach, research sampling using purposive sampling totaling 25 respondents based on inclusion criteria, research instruments using observation sheets and digital sphygmomanometer. Progressive muscle relaxation was carried out for 3 days and measured before and after the intervention. Data were analyzed using paired t test. The results of this study showed that the average blood pressure before the intervention was 162/100mmHg and the average blood pressure after the intervention was 151/91mmHg which means there is a significant decrease in blood pressure after progressive muscle relaxation intervention with a p value = 0.000 (<0.05). This research is expected to be a new point of view and knowledge for various parties, especially as a reference for the development of complementary therapies at the old deli health center in the future.